A software-rel kapcsolatos alapvető szabályok nemzetközi aspektusból – különös tekintettel a német jogi megoldásokra - Papp, Tekla; Auer, Ádám (Debreceni Jogi Műhely, 2014)
Competion in the field of Informational Techonology influences our everyday life; a competion realized in a global playground, not reduced into a national framework. Joining the discussion around optimal software protection, we introduce some foreign software regulations in our essay from different given aspects, and finally we analyse German legal solutions regarding softwares. Observation of foreign regulations related to softwares and their protection is needed because there are still a lot of unanswered questions around software as a legal instrument. Inadequacy of copyright to serve protection of softwares and the need to create sui generis protection come up in the latest researches. Furthermore, the number of inventions supported by IT and the number of software supported technological solutions increase in our days, and that moves this legal instrument into the field of patent jurisdictions and industrial property. Efficient legal protection is both a tool and a goal in the system, since elaboration and support of genuine ideas are priority interests. According to our opinion, it is not only the task but also the obligation of private law – as the law regulating basic rights of natural persons and legal entities in personal and financial context – to set up proper regulation in this system.